2018
DOI: 10.26603/ijspt20180104
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Different Anterior Thigh Self-Massage on Hip Range-of-Motion in Trained Men

Abstract: Background: Self-massage is a ubiquitous intervention similar to massage, but performed by the recipient him-or herself rather than by a therapist, most often using a tool (e.g., foam roller, roller massager). Self-massage has been found to have a wide range of effects. It is particularly known for increasing flexibility acutely, although not always. The variability of the results in previous studies may potentially be a function of the tool used. Recent findings also suggest that self-massage exerts global ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
0
15
1
1
Order By: Relevance
“…However, the vast majority of articles published since January 2018 confirm the pooled effects of FR, which are calculated in this meta-analysis. For example, Cheatham and Stull (2018), de Souza et al (2019), Hall and Chadwick Smith (2018), Killen et al (2018), Macgregor et al (2018), Madoni et al (2018), Monteiro et al (2018, 2019a,b), and Smith et al (2018, 2019) were able to confirm that FR can improve flexibility, perceived muscle pain perception, and/or the recovery of strength performance, while Madoni et al (2018) found that FR had no effect on jump performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the vast majority of articles published since January 2018 confirm the pooled effects of FR, which are calculated in this meta-analysis. For example, Cheatham and Stull (2018), de Souza et al (2019), Hall and Chadwick Smith (2018), Killen et al (2018), Macgregor et al (2018), Madoni et al (2018), Monteiro et al (2018, 2019a,b), and Smith et al (2018, 2019) were able to confirm that FR can improve flexibility, perceived muscle pain perception, and/or the recovery of strength performance, while Madoni et al (2018) found that FR had no effect on jump performance.…”
Section: Discussionmentioning
confidence: 99%
“…This may be partly due to the fact that few studies have examined the underlying physiological mechanisms of FR. Nevertheless, the potential effects of FR have been attributed to mechanical, neurological, physiological, and psychophysiological parameters (Aboodarda et al, 2015; Cavanaugh et al, 2017; Monteiro et al, 2018; Phillips et al, 2018). The mechanical mechanisms are comprised of a number of sub-mechanisms, such as reduction in tissue adhesion, altered tissue stiffness, and thixotropic responses (Aboodarda et al, 2015; Kelly and Beardsley, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This was performed using the three measurements for each variable recorded at baseline. The minimal detectable change (MDC) was then calculated as 1.96( ) √2 (Monteiro, Vigotsky, da Silva Novaes, & Škarabot, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, effect sizes (Cohen's d) were calculated 29 and interpreted as: < 0.25 = trivial, 0.25-0.50 = small, 0.50-1.0 = moderate, and > 1.0 = large, given participants' longstanding participation in the sport. 30 To evaluate individual responses, players exhibiting changes in excess of the minimal detectable change (MDC) -calculated as [(1.96xSEM)x√2] 31 were classified as 'positive' or 'negative' responders (dependent on the direction of change). Changes < MDC were classified as 'neutral' responses.…”
Section: Statistical Analysesmentioning
confidence: 99%